Characteristic and phylogenetic analyses of chloroplast genome for Syringa komarowii C.K.Schneid. (Oleaceae) from Huoditang, China, an important horticultural plant - Yong-Qin Cheng; Zai-Min Jiang; Jing Cai (Mitochondrial DNA. Part B. Resources, 2021)
The genus Syringa (Oleaceae) comprises some of the most important cultivated horticultural trees worldwide. Syringa komarowii, is one of these important horticultural plants. We sequenced the complete chloroplast (cp) genomes of S. komarowii (previously identified as var. reflexa) using Illumina Hiseq X Ten platform. The cp genome exhibits a typical quadripartite structure with 158,020 bp in length, which consists of two copies of inverted repeat (IR) regions (25,676 bp) separated by a large single copy (LSC) region (87,628 bp) and a small single copy (SSC) region (19,040 bp). The cp genome of S. komarowii encodes a total of 132 genes, including 88 protein-coding genes, 36 tRNA genes and 8 rRNA genes. A maximum likelihood (ML) phylogenetic analysis resolved that S. komarowii in a clade with S. wolfii and S. yunnanensis. The ML tree also showed Syringa appeared more closely related to Ligustrum than to the other genera in the Oleaceae.